A Force-Position Control System Based on Soft Tissue under Large Deformation. (13th June 2013) - Hu, Lei; Zhang, Jie; Li, Changsheng; Cui, Yan; Wang, Liquan
Abstract : We introduce an extension of the mass-spring model applied to human tissue that can truly reflect the mechanical properties of a living person's tissue under large deformations under pressure by a massage head. The model is used in the force-position control system and helps us to control the massage force more accurately. Parameters of the model were determined according to the experimental results. Simulation results demonstrated that the model succeeded in modeling living tissue under large deformation, and the force-position control system based on the soft tissue model under large deformation achieved higher accuracy than the control system based on the soft tissue model with constant stiffness.